Storying the Past, Creating the Future: Hope and Narrative Openness in a Writing Group for Older Women - Mills, Kelly J.; Nicol, Jennifer J.; Murphy, M. Shaun (Canadian Journal of Counselling and Psychotherapy, 2020)
Studies on the therapeutic impacts of writing and sharing stories in older adulthood have focused on groups facilitated by professionals. The present inquiry sought to investigate the experiences of older women in a grassroots, community-based writing group. Participants were three women writers aged 79 years and older. Their experiences with their group were encountered using a narrative inquiry approach that involved semi-structured interviews, writing samples, and field notes. The women’s practice of writing and sharing stories with female peers was understood to enhance their hopefulness for the future and their sense of agency. This inquiry extends research on creativity and well-being in older adulthood, emphasizing the therapeutic implications of older adults leading their creative practices in group settings.